Influence of Temperature and Particle Size on Heating Value of Biobriquette from Rubber Seed - Tiara Armita; Sri Haryati; Risfidian Mohadi; Puteri Kusuma Wardhani (Science and Technology Indonesia, 2019)
Rubber seed as a biomass is potentially used as the source of alternative energy in briquette. Previous research had found that rubber seed briquette has the highest heating value of 6287,8 cal/g. It can be increased by varying temperature and mesh size. In this research, the effect of temperature and particle size on the amount of heat of rubber seed biobriquette from Muarakuang (Batu Raja) was investigated. It was done in Politeknik Negeri Sriwijaya Palembang laboratory. Proximate analysis was executed in Politeknik Negeri Sriwijaya Palembang coal laboratory. The temperature varied of 250 oC, 500 oC, and 750 oC with the particle size varied by 80 mesh, 120 mesh, and 200 mesh. Quality test of fabricated biobriquette consisted of proximate analysis such as calorific value, inherent moisture, ash ratio, volatile matter ratio, and fixed carbon ratio. The highest of heating value was 6836 cal/g from biobriquette sample were found under particle size of 80 mesh and temperature of 250 oC. The heating value reached 5371 cal/g which the particle size was 200 mesh and temperature of 750 oC. The heating value of biobriquette were compared with Indonesian National Standardization (SNI), which met with the standard of heating value (5000 cal/g).